Combustion performance and emission characteristics on HCCI engine of waste plastic pyrolysis oil biodiesel blends with external PFI and vaporiser. Issue 3 (3rd May 2020) - Ramavathu, Jyothunaik; Kota, Thirupathi Reddy
ABSTRACT: Analysis of plastic oil obtained from waste plastic through pyrolysis process, as an alternative to biodiesel is presented in this paper. The HCCI engine is considered for experimental validation of combustion performance and emission characteristics. To accumulate pyrolysis oil as fuel, the design modifications were made in external mixture formation on the existing computerised 4-stroke, single cylinder, water cooled, direct injection kirloskar diesel engine connected with eddy current dynamometer to satisfy HCCI conditions. HCCI engine can be worked on wide assortment of fuels beginning from diesel to different blends (WPPO 5%, 10%, 15% and 20% by volume) of biodiesel .The designed additional device connected to the engine is utilised for fuel vaporisation and mixture arrangement. In the experimental study, the combustion results were initiate to be of 39.69 % higher Rate of Heat Release (RoHR) for biodiesel HCCI as compared with diesel HCCI. Higher brake thermal efficiency (BTE) was found 37 % without exhaust gas recirculation (EGR) at WPPO 20 % biodiesel blend. And also found 50 % and 65 % reduction in NOx emission and 18 % and 28 % reduction in smoke opacity are obtained for biodiesel vapour induction without EGR and biodiesel vapour induction with 15 % EGR as compared with diesel fuel. The CO (0.34 %), and UHC (2.15 %) emissions are increases with 15 % EGR, but the emissions are within the standard limits specified by the emissions standards.